Pola Komunikasi Budaya Pada Tradisi Ngelengkak Dalam Membangun Kerukunan Keluarga - Sinta Nuriah; Wisri (Maddah : Jurnal Komunikasi dan Konseling Islam, 2022)
This paper is a description of the cultural communication carried out by the Lombok people related to the ngelengkak tradition that developed in the local community. The communication process carried out gave birth to a communication pattern. The ngelengkak tradition is held with the aim of building family harmony. The purpose of this study was to describe the pattern of cultural communication in the ngelengkak tradition in building family harmony. This study uses a qualitative research method with a phenomenological research model.The results of this study are that intercultural communication in the ngelengkak tradition in building family harmony in Darek Village can create togetherness to always respect and respect each other’s opinion in various situations and conditions. So that they can establish a peaceful, prosperous and harmonious family life through a process of tradition or culture which is the value of a future life.